Identidade futebolística: os torcedores "Mistos" do Nordeste - Vasconcelos, Artur Alves de (2011)
There is a profile of soccer fans which usually supports a team from its state and another club, based in a different region. This kind of fan is pejoratively called “misto” (mixed). This appellation was created by fans who disagree with this way of cheering. The fan called “misto” exists in all the Brazilian states. Because of this, since 2008 some groups of fans, non “mistos”, started to organize sashes, shirts, videos and virtual communities to show their point of view and encourage the “mistos” to support only a team from its state. This mobilization, known “anti-misto”, started in Northeast. One of its most popular watchwords is “A vergonha do Nordeste” (The shame of Northeast). This report aims to understand some of the social, historic and subjective situations that stimulated the advent of the fans called “misto”, analysing the Northeast case. Analysing Brazilian soccer as a field (Bourdieu), it could find some teams that holds the main types of capital and are more actives in the institutions. They are dominants. These teams belong to Rio de Janeiro and São Paulo. The clubs from Northeast and other regions are dominated. The dominants are very attractive for the fans, who also found in the choice for a soccer team a way to conquest recognition and distinction. The main TV networks in Brazil are based in São Paulo and Rio de Janeiro. Using their net of affiliated TVs across the country, they give daily to soccer fans from every regions a lot of information about the teams from São Paulo and Rio de Janeiro, including live transmit from their participation in national and international competitions. This constant presence in media makes these teams symbolically close to the routine of the Northeast fan, although geographically distant. Because of this proximity, the “misto” doesn’t see that teams as clubs which belong to other people (an “anti-misto” recurrent argument), but as something to which he could belong.